30‐3: Student Paper: Polarization State Exploration and Management in Waveguide Display with Polarization Volume Gratings. Issue 1 (28th June 2021) - Feng, Xiayu; Lu, Lu; Lee, Yun-Han; Yaroshchuk, Oleg; Silverstein, Barry; Bos, Philip
Abstract : In this work, we focus on the polarization state input, propagation and output of waveguide display device using polarization volume holographic gratings (PVH) as couplers. First, a detailed study of the transmissive PVH (T‐PVH) is presented in terms of diffraction efficiency, polarization selectivity and polarization output, which is expected to be used as the waveguide input/output couplers. The configuration here called "Slanted T‐PVH" has the advantageous property of maintaining orthogonal circular output polarization states. Then, the polarization state management of light propagating in waveguide is considered. The issue that the polarization state of the light can change as it propagates in the waveguide due to total internal reflection (TIR) is made clear, that has a negative effect on the waveguide PVH input/output couplers efficiency, image uniformity, and the polarization multiplexing capability. Finally, it is shown that applying compensators to correct the polarization state change can solve the polarization state change in a waveguide.